2016 IEEE-APS Topical Conference on Antennas and Propagation in Wireless Communications (APWC) 2016
DOI: 10.1109/apwc.2016.7738146
|View full text |Cite
|
Sign up to set email alerts
|

An extremely wideband tapered balun for application in tightly coupled arrays

Abstract: − This paper presents the design of a single layer, compact, tapered balun with a >20:1 bandwidth and less than / in length at the lowest frequency of operation. The balun operates from 0.7GHz to over 15GHz. It can provide both impedance transformation as well as a balanced feed for tightly coupled arrays. Its performance is compared with that of a full-length balun operating over the same frequency band. There is a high degree of agreement between the two baluns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 11 publications
(12 reference statements)
0
5
0
Order By: Relevance
“…When a CPS line of length 10 mm is added to the curved taper line, the total length of the BALUN is extended by 10 mm. It can be observed that the proposed structure of the BALUN outperforms all the BALUNs in terms of size and % bandwidth, excluding the BALUNs given by Bah (2016), Lin et al (2015 and Lee et al (2018). These three BALUNs are smaller than the proposed curved BALUN.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…When a CPS line of length 10 mm is added to the curved taper line, the total length of the BALUN is extended by 10 mm. It can be observed that the proposed structure of the BALUN outperforms all the BALUNs in terms of size and % bandwidth, excluding the BALUNs given by Bah (2016), Lin et al (2015 and Lee et al (2018). These three BALUNs are smaller than the proposed curved BALUN.…”
Section: Resultsmentioning
confidence: 82%
“…A dipole antenna with both arms on opposite sides of a substrate was excited using an asymmetric MS line BALUN transformer. This BALUN comprised a taper ground plane connected to one arm of the dipole and the MS line of the BALUN connected to the other arm of the dipole present on the other side of the substrate (Bah, 2016). Impedance transformation using a taper transmission line technique is not restricted to printed technology but also extends to the coaxial transmission line (Vega et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Typically, tapered baluns that are avoided because of their length. However, contrary to the design presented in [5], [26], the proposed balun design combines both mode transduction and impedance transformation similarly to [27]. This approach allows wider bandwidth while limiting the aperture depth under the ground plane (λ low /14.5), a Klopfenstein tapered profile is designed using a Bézier curve approximation.…”
Section: :1 Klopfenstein Tapered Balunmentioning
confidence: 99%
“…However, the four-arm sinuous antenna is disadvantageous for wideband operation because of the loss due to the need for a long wideband balun for high input impedance ( 267) [11], [12]. To address these flaws, various miniaturization techniques for the balun have been investigated [13], [14]. However, these techniques are not appropriate for use in sinuous antennas because it deteriorates the baluns' balancing properties, which adversely impact the antenna performance.…”
Section: Introductionmentioning
confidence: 99%